Effect Of Hole Size, Sheet Thickness And Material Type To The Performance Of The Self-Clinching Fastener - Daud, Nurul Ain Mat (Universiti Sains Malaysia, 2019)
The reliability of a self-clinching fastener in an application depends on several factors, starting with a properly sized hole, the thickness and hardness of the host panel. Correct installation and design of the fastener as well as the application wherever the fastener is applied also play a role. Self-clinching fasteners are well-suited for working with thin metal sheets such as in the production of automobile parts as well as modern communication devices like smartphone and computers. The ultimate strength of the mating clinching fastener with base material needs to be ensured sturdy to produce a strong assembly. In this project, the effect of holes geometries, sheet thickness and material type of the mating panel was studied on the performance of one of the self-clinching fasteners which are nut by conducting a torque-out test on the mating panel and nut. The testing was conducted at five level factors of parameters. A test rig was fabricated to firmly hold the panels during the torque-out test on the semi-auto torsion machine. The torque-out test was performed until the nut rotate or fail within the panel and torque values for each test panels were recorded using PicoLog recorder. The level of significance and optimal combination of parameters for the torque-out test were analysed based on Taguchi Method. The analysis revealed that hole diameter is the most significance parameters to the nut’s performance for both Mild Steel and Aluminium 5052 host panel. In comparing both materials of panel, material types shows the highest significance compared to sheet thickness and hole diameter. In addition, for mild steel host panel, the optimal combination of parameters for maximum performance of the nut in its application are on the panel thickness of 3 mm and hole diameter of 8.71 mm. While, for Aluminium 5052 host panel, thickness of 3 mm and hole diameter of 8.83 mm. For the combined analysis of Mild Steel and Aluminium 5052 host panel, the maximum performance can be found on Mild Steel host panel with thickness of 2 mm and hole diameter of 8.71 mm.